2022
DOI: 10.3390/life12030356
|View full text |Cite
|
Sign up to set email alerts
|

Piceatannol Affects Gastric Ulcers Induced by Indomethacin: Association of Antioxidant, Anti-Inflammatory, and Angiogenesis Mechanisms in Rats

Abstract: One of the major aggressive factors that affect gastric injury is non-steroidal anti-inflammatory drugs (NSAIDs). Indomethacin (Indo) showed higher potentiality in gastric injury over conventional NSAIDs. Piceatannol (PIC) is a natural polyphenolic stilbene that possesses potent antioxidant and anti-inflammatory properties. The gastroprotective properties of PIC have been overlooked previously. Hence, we aim to study gastric injury induced by Indo and the protective action manifested by PIC, as well as to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The NF‐κB expression was paralleled by a strong COX‐2 expression in the same animal group. In accordance, Mostafa et al 3 and Shaik and Eid 38 recorded an overexpression of NF‐κB and COX‐2 in a parallel model of gastric ulceration. Soyasaponin I treatment showed a marked reduction in the mean area percent of NF‐κB and COX‐2 immunoexpression, and a similar effect was observed at the gene level.…”
Section: Discussionsupporting
confidence: 71%
“…The NF‐κB expression was paralleled by a strong COX‐2 expression in the same animal group. In accordance, Mostafa et al 3 and Shaik and Eid 38 recorded an overexpression of NF‐κB and COX‐2 in a parallel model of gastric ulceration. Soyasaponin I treatment showed a marked reduction in the mean area percent of NF‐κB and COX‐2 immunoexpression, and a similar effect was observed at the gene level.…”
Section: Discussionsupporting
confidence: 71%
“…The malignancies and the inflammatory reactions are the general outcomes of the toxicity of insecticides and pesticides. Non-steroidal anti-inflammatory drugs (NSAIDs) are the most extensively used analgesic and anti-inflammatory drugs but these are also the major causative agent that not only induces gastric damage but via various mechanisms, also delay the process of healing 3 . The topic of detoxification of these chemicals remained the topic of interest for the avoidance of such health damage.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, this study revealed the effects of Cur on the oxidative stress, inflammation, and apoptosis of gastric epithelial cells. Cur has also been reported to ameliorate bone loss by affecting mesenchymal stem cell fate in aging mice [17]. Furthermore, Cur promotes osteogenic differentiation, preventing ovariectomized-induced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%